Factors influencing family business performance on the stock exchange of Thailand - Aitsaranukuldet, Sasikarn; Sudharatna, Yuraporn (Kasetsart Journal of Social Sciences, 2016)
The objectives of this study were to study financial and non-financial factors that influence the performance of family businesses. The sample size consisted of 102 family businesses on the Stock Exchange of Thailand. Secondary data from the period 2008 to 2012 in terms of financial ratios and a questionnaire survey were used in this research. The statistical analysis consisted of the frequency, percentage, mean, standard deviation, and stepwise multiple regression analysis. The findings revealed that the asset management ratio, leverage ratio, profitability ratio, and growth have an influence on the performance of family businesses. The satisfaction of family businesses was based on non-financial factors that have an effect on the performance of family businesses.